2004
DOI: 10.1521/jscp.23.3.377.35457
|View full text |Cite
|
Sign up to set email alerts
|

Examining Two Aspects of Contact on the Stigma of Mental Illness

Abstract: This study expands on earlier research by our group that has shown that contact with people with mental illness has significant effects on changing stigmatizing attitudes. Two factors that affect contact are examined in this study: the medium through which contact is experienced, and the level of stereotype disconfirmation engendered in contact. One hundred sixty-four individuals were randomly assigned to one of five conditions. Three of the conditions allowed us to examine the effects of medium: no stigma-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
169
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 30 publications
13
169
0
1
Order By: Relevance
“…Reinke et al [48] found the same effect at post-test measurement using a social distance scale; Clement et al [25] also conducted a follow-up measurement and the effect measured by four different scales persisted at four months. Both video intervention and direct contact intervention in these two studies had the same structure and content, which was a narrative of a person with mental illness.…”
Section: Is Video Intervention Effective Compared To Other Interventimentioning
confidence: 88%
See 1 more Smart Citation
“…Reinke et al [48] found the same effect at post-test measurement using a social distance scale; Clement et al [25] also conducted a follow-up measurement and the effect measured by four different scales persisted at four months. Both video intervention and direct contact intervention in these two studies had the same structure and content, which was a narrative of a person with mental illness.…”
Section: Is Video Intervention Effective Compared To Other Interventimentioning
confidence: 88%
“…Seven studies compared video intervention to some other type of intervention; five of them compared video intervention to direct contact [25,40,41,48,57], three compared video to an educational session [25,58], one to a session where the experience of hallucinations was simulated and experienced by the study population [42].…”
Section: Is Video Intervention Effective Compared To Other Interventimentioning
confidence: 99%
“…Although filmed interventions have been used to try to alleviate mental illness associated stigma in other populations (Chan et al 2009;Faigin and Stein 2008;Penn et al 2003;Reinke et al 2004), the specific film in this study has not been used or studied previously for this purpose. Compared to the films used in other intervention studies (whose content has comprised: education about mental illness conditions, interviews of individuals with mental illness, documentaries following people with mental illness and their families, theatrical performance concerning issues related to living with a mental illness, post-treatment experiences of people with mental illness, disconfirmation films that highlighted the similarities of people with and without a mental illness, dramatized portrayal of daily activities, and opinions from support people including family, friends, and colleagues) this film provides a different perspective on the lived experience of mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Of the three levels at which stigma operates, public stigma (defined as the phenomenon whereby large social groups have negative attitudes towards and beliefs about, and even act against those with a disenfranchised trait -like mental illness (Corrigan and Watson 2002)) has received the greatest attention. Public stigma related to mental illness has been investigated in a broad range of groups including the general public Kobau et al 2009), students (Brown 2008;Chan et al 2009;Corrigan et al 2001;Faigin and Stein 2008;Mann and Himelein 2008;Penn et al 1994;Reinke et al 2004) police , and mental health workers Schulze 2007). In all groups in which public stigma has been investigated, negative beliefs about, and attitudes and behaviors towards individuals with mental illness have been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation